New records of the Tabebuia Alliance (Bignoniaceae) for the state of Paraiba, northeastern Brazil - Isabella Johanes N. Brito; Swami L. Costa; Joel Maciel P. Cordeiro; Lúcia G. Lohmann; José Iranildo M. de Melo (Revista Mexicana de Biodiversidad)
This study presents 3 new records of the Tabebuia Alliance (Bignoniaceae) for the state of Paraiba, northeastern Brazil: Godmania dardanoi (J. C. Gomes) A. H. Gentry, Handroanthus umbellatus (Sond.) Mattos and Tabebuia stenocalyx Sprague & Stapf. These species were found in preserved areas of Atlantic rain forest, growing in swampy areas, on sandy and clay soils, and flowering between December and June. For each new record for the state of Paraiba, we present detailed descriptions, taxonomic notes, geographic distribution and photographs.